Implementation of Extreme Programming (XP) in the Development of Dental Clinic Information Systems - Bintang Pramudya; Dinda Chesar Putri Ramadhani; Hilda Nuzulul Mujaddidah; Risqy Siwi Pradini (Journal of Enhanced Studies in Informatics and Computer Applications, 2025)
Along with the development of information technology, dental clinics are required to improve efficiency and quality of service through an integrated information system. This study aims to develop a web-based Dental Clinic Information System using Laravel with the Extreme Programming (XP) method as its development approach. This system is designed to manage electronic medical records, examination schedules, drug stock, and patient bills efficiently, according to the Regulation of the Minister of Health of Indonesia Number 24 of 2022 concerning electronic medical records. This research method involves four stages in XP: planning, design, coding, and testing. At the design stage, Use Case and Activity Diagram modeling are created to ensure the system meets user needs. The system implementation uses Laravel Filament to build an integrated admin dashboard. Testing is carried out using Black-Box Testing to ensure all features function properly. The results of the study show that the developed system can improve the operational efficiency of dental clinics, reduce manual recording errors, and speed up the administration process. With the XP approach, system development becomes more flexible and adaptive to changes in user needs. It is hoped that this system can be applied in small to medium-scale dental clinics to improve the quality of health services.